Asylum seeking and irregular migration - Slobodan Djajić (Graduate Institute of International and Development Studies, 2014)
This paper develops a model of optimizing behavior of asylum seekers whose objective is to reach an advanced country. Their personal characteristics and the challenges anticipated along the way determine whether they try to reach the ultimate destination with the aid of human smugglers or by applying for resettlement with the United Nations High Commissioner for Refugees (UNHCR). In the current policy environment, individuals who are relatively young, skilled, wealthy, and have access to credit from the family network are found to have a strong incentive to choose the undocumented migration option.
Keywords: F22; 330; asylum seekers; illegal immigration